Fabrication of a cost-effective polymer nanograting as a disposable plasmonic biosensor using nanoimprint lithography. (21st July 2017) - Mohapatra, Saswat; Kumari, Sudha; Moirangthem, Rakesh S.
Abstract: A simple and cost-effective flexible plasmonic sensor is developed using a gold-coated polymer nanograting structure prepared via soft UV nanoimprint lithography. The sub-wavelength nanograting patterns of digital versatile discs were used as a template to prepare the polydimethylsiloxane stamp. The plasmonic sensing substrate was achieved after coating a gold thin film on top of the imprinted nanograting sample. The surface plasmon resonance (SPR) modes excited on the gold-coated nanograting structure appeared as a dip in the reflectance spectrum measured at normal incidence under white light illumination in the ambient air medium. Electromagnetic simulation based on the finite element method was carried out to analyze the excited SPR modes. The simulated result shows very close agreement with the experimental data. The performance of the sensor with respect to changing the surrounding dielectric medium yields a bulk refractive index sensitivity of 788  ±  21 nm per refractive index unit. Further, label-free detection of proteins using a plasmonic sensing substrate was demonstrated by monitoring specific interactions between bovine serum albumin (BSA) and anti-BSA proteins, which gave a detection limit of 123 pg mm −2 with respect to target anti-BSA protein binding. Thus, our proposed plasmonic sensor has potential for the development of an economical and highly sensitive label-free optical biosensing device for biomedical applications.